Les enjeux de la traduction - Markowski, Grzegorz (Verbum – Analecta Neolatina, 2024)
Translation has a long history, dating back to antiquity, playing a key role in intellectual mediation and the dissemination of ideas, especially during the Renaissance. Today, it addresses contemporary challenges while facilitating intercultural understanding and preserving linguistic diversity. Economically, it enables the expansion of international markets, improves communication and ensures regulatory compliance, providing competitive advantages. In the digital age, translation connects cultures globally through advanced technologies. The future of translation relies on AI and automated translation, providing real-time translations and cultural adaptation, while raising crucial ethical questions.